Insights into the performance of the two contrasting dynamic adsorption platforms in the removal of gaseous benzene on microporous carbon materials. (1st September 2022) - Wang, Xinzhi; Anand, Bhaskar; Kim, Ki-Hyun; Younis, Sherif A.
Abstract: A high-speed purification system made of packed-bed adsorber is often subject to apparent demerits (e.g., pressure drop and/or high energy consumption) when treating waste gas. As a potential alternative to such system, a denuder sorbent tube has been constructed by coating powder-activated carbon (PAC) on the inner surface of the sorbent tube with the help of polyvinyl alcohol (PVA) as adhesive. The designed denuder sorbent tube was then used to treat a gaseous stream containing 1 Pa benzene (as a model volatile organic compound (VOC)) under various volumetric flow rates (100–500 mL·min −1 ). The results revealed that the designed packed bed outperformed the denuder system by a factor of at least two (in terms of the breakthrough volume (BTV, L·g −1 ) and adsorption capacity (Q, mg·g −1 ) at 10% BT) when tested at upper flow rates (200–500 mL·min −1 ). In contrast, the pattern was reversed at the lowest flow rate of 100 mL·min −1 so that the denuder (BTV 10%  = 615 L·g −1 ) outperforms the packed bed (330 L·g −1 ). According to the adsorption kinetic analysis, the surface-interaction and film diffusion have a rate-determining adsorption step in the denuder, while the boundary/pore diffusion mechanism should play a crucial role in the packed-bed system. Overall, the PAC-based denuder system is recommendable in removing VOCs at or near ambient conditions as an efficient alternative to replace traditional packed-bed columns. Graphical abstract: Image 1